Impact of environment regulation on the efficiency of regional construction industry: A 3-stage Data Envelopment Analysis (DEA). (1st November 2018) - Zhang, Jingxiao; Li, Hui; Xia, Bo; Skitmore, Martin
Abstract: Although the impact of environmental regulation on industrial efficiency has been widely investigated in various industries, it remains largely unknown in the construction industry. Using 2011–2015 panel data of 30 provinces and cities in China, this paper aims to reveal whether environmental regulation has an impact on regional construction efficiency. A 3-Stage DEA Model is used to measure the technical efficiency of regional construction industries influenced by environmental regulations. Then Hansen's (Hansen, 1999) threshold regression model is used to analyse the threshold effect of environment regulation on the efficiency of regional construction industry. A single threshold value of 0.014 is identified to be used to group China's 30 provinces into high-regulation and low-regulation regions. The results show that environmental regulation has a significant impact on the efficiency of China's construction industry. Scale efficiency is the most affected. The technical efficiency of highly regulated provinces is less affected by environmental regulations. The findings provide a reference frame and analytical method for the analysis of construction efficiency of other developing countries, and provide practical implications for the implementation of environmental regulation policies and future policy formulation. Highlights: The impact of environment regulation on China's construction industry is evaluated. Hansen's threshold regression model is used to group provinces by regulation level. A single threshold p -value of 0.014 is identified for grouping provinces. Environment regulation significant impacts construction industry efficiency. Environment regulation affects high regulated provinces' technical efficiency less.